1970
DOI: 10.3329/bjar.v35i1.5880
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of three insecticides against mustard aphid and predator under field condition

Abstract: Studies were conducted in the field to determine the effectiveness of three insectidicdes, Metasystox-R 25EC, Dimethion 40 EC, and Fentro 50 EC applied against mustard aphid, Lipaphis erysimi Kalt. and measure their toxic action on the predator Coccinella septempunctata L. The mustard plants were sprayed with the insecticides at 0.05% and 0.025% a. i. at 50 and 70 days after sowing. The mortality of both mustard aphid and the predator was assessed at 1, 4, and 7 days after first and second spraying of insectic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…All the findings are more or less in agreement with the findings of the present study. Few variation were found which might be due to the variation of doses of insecticides and place (Maula et al 2010).…”
Section: Resultsmentioning
confidence: 99%
“…All the findings are more or less in agreement with the findings of the present study. Few variation were found which might be due to the variation of doses of insecticides and place (Maula et al 2010).…”
Section: Resultsmentioning
confidence: 99%
“…Youn et al (2003) also observed that Thiamethoxam was most effective in controlling L. erysimi population. Maula et al (2010) found that Oxydemeton methyl 25EC was most effective among the three insecticides causing the highest mortality of mustard aphid followed by Dimethioate 40EC. But they observed lowest mortality of Coccinella septempunctata in Dimethoate 40EC treated plots.…”
Section: Discussionmentioning
confidence: 99%
“…(Rana et al, 2007) reported that carbosulfan, bifenthrin and imidacloprid were effective for management of mustard aphid. (Maula et al, 2010) conducated field trials to determine the efficacy of three insecticides against L. erysimi and C. septempunctata. In their results, highest mortality of L. erysimi was recorded in Metasystox-R treated plots, while lowest mortality of C. septempunctata was observed in Dimethion treated plots.…”
Section: Amin Et Al Effect Of Different Insecticides Against Insect mentioning
confidence: 99%